Transgenerational plasticity as a mechanism of response to marine heatwaves in the purple sea urchin, Strongylocentrotus purpuratus - Chamorro, Jannine D.; McDonald, Adriane M.; Hofmann, Gretchen E. (Frontiers in Marine Science, 2023)
Kelp forests of the California Current System have experienced prolonged marine heatwave (MHW) events that overlap in time with the phenology of life history events (e.g., gametogenesis and spawning) of many benthic marine invertebrates. To study the effect of thermal stress from MHWs during gametogenesis in the purple sea urchin (Strongylocentrotus purpuratus) and further, whether MHWs might induce transgenerational plasticity (TGP) in thermal tolerance of progeny, adult urchins were acclimated to two conditions in the laboratory – a MHW temperature of 18°C and a non-MHW temperature of 13°C. Following a four-month long acclimation period (October–January), adults were spawned and offspring from each parental condition were reared at MHW (18°C) and non-MHW temperatures (13°C), creating a total of four embryo treatment groups. To assess transgenerational effects for each of the four groups, we measured thermal tolerance of hatched blastula embryos in acute thermal tolerance trials. Embryos from MHW-acclimated females were more thermally tolerant with higher LT50 values as compared to progeny from non-MHW-acclimated females. Additionally, there was an effect of female acclimation state on offspring body size at two stages of embryonic development - early gastrulae and prism, an early stage echinopluteus larvae. To assess maternal provisioning as means to also alter embryo performance, we assessed gamete traits from the differentially acclimated females, by measuring size and biochemical composition of eggs. MHW-acclimated females had eggs with higher protein concentrations, while egg size and lipid content showed no differences. Our results indicate that TGP plays a role in altering the performance of progeny as a function of the thermal history of the female, especially when thermal stress coincides with gametogenesis. In addition, the data on egg provisioning show that maternal experience can influence embryo traits via egg protein content. Although this is a laboratory-based study, the results suggest that TGP may play a role in the resistance and tolerance of S. purpuratus early stages in the natural kelp forest setting.